KONTRIBUSI BURUH PEREMPUAN TERHADAP PENDAPATAN KELUARGA (STUDI KASUS TEMPAT PELELANGAN IKAN DI TUMUMPA KOTA MANADO) - Jilly B.C. Sinadia; Welson M. Wangke; Noortje M. Benu (Sam Ratulangi University, 2017)
Problems in research is needs economy of a family the average at the Tumumpa II not enough because the head of the household income is relatively low, so as to meet the needs of a family housewieves at the Tumumpa II trying to provided for by working as woman. Research aims to understand how much contribution given by women who work as a fish. Research carried out in October until December 2016. The data of this research were primary and secondary data. The primary data was obtained through interviews directly to 46 respondents using kuisoner and secondary data obtained from office fisheries and marine and the village office Tumumpa II. The sample technique is purposive sampling the techniques with based on criteria respondents were women who own husband or and married wit responsibility for in the family. Data generated presented in the form of table and described the contribution given by workers women. To know the contribution given by workers women obtained from the percentage of income husband and wife and the son (who have worked). The result showed that woman sho worked as labarers carrying fish contributed for 44,90%. This means that the contribution of income of family income at the Tumumpa II big enough, what is mean by big enough is on the income female by working as laborers have been very helpful husband by meet and sufficient need in housholds every day.